Development of copper-catalysed addition reactions to alkynes - Tan, QW (2019)
In this thesis, new copper-catalysed addition reactions to alkynes have been developed. The new methodologies exploit hydro-functionalisation to transform readily available starting materials into N-heterocycles and enol esters via addition of amides and acids to alkynes, respectively. Chapter 1 is a literature review covering the transition metal-catalysed hydroamination and hydro-oxycarbonylation of alkynes, and some of the well-known copper-catalysed reactions. Chapter 2 documents our new methodology on exploiting the copper-catalysed hydroamination of terminal alkynes to synthesis 5-ylidenepyrrol-2(5H)-ones and 5-hydroxypyrrol-2(5H)-ones, using readily available α-keto amides and terminal alkynes. A method towards the synthesis of asymmetric maleimides is also reported.